Portable grazing exit X-ray fluorescence system using a low-power X-ray tube - Ramon Silva dos Santos; Davi Ferreira de Oliveira; Joaquim Teixeira de Assis; Marcelino José dos Anjos (Brazilian Journal of Radiation Sciences, 2019)
In this work was developed a portable system of grazing exit X-ray fluorescence (geometric 90° - 0°) that can be applied in several areas science and technology. GE-XRF portable system is formed by a mini X-ray tube of low power (anode of Au) and a SiPIN detector. The reflectors used as sample support (sampler carrier) were quartz discs. The grazing exit angle was experimentally determined by measuring a cooper solution (10 μg.g-1). The accuracy of the system was checked using multielement reference solution as standard reference material. The relative errors between measured and certified values are in the range of 4 to 19%. The first results showed a background was drastically reduced at grazing exit angles, enabling trace elemental analysis. The system of GE-XRF proved to be quite stable and reproducible. This paper shows that it is possible to produce a portable system of grazing exit X-ray fluorescence compact, efficient, low-cost and easy-to-handle instrumentation using a low power X-ray tube and a SiPIN compact detector.